Validation of the Malay version of the multidimensional scale of perceived social support (MSPSS-M) among a group of medical students in Faculty of Medicine, University Malaya - Ng, C.G.; Amer Siddiq, A.N.; Aida, S.A.; Zainal, N.Z.; Koh, O.H. (2010)
Objective: The aim of this study was to validate the Malay version of the Multidimensional Scale of Perceived Social Support (MSPSS-M) among a group of medical students in Faculty of Medicine, University Malaya. Methods: 237 students participated in the study. They were given the Malay version of MSPSS, medical outcome study (MOS) social support survey, Malay version of General Health Questionnaire (GHQ), Malay version of Beck Depression Inventory (BDI) and English version of MSPSS. A week later, these students were again given the Malay version of MSPSS. Results: The instrument displayed good internal consistency (Cronbach's alpha = 0.89), parallel form reliability (0.94) and testâretest reliability (0.77) (Spearman's rho, p < 0.01). The negative correlation of the total and subscales of the instrument with the Malay version of GHQ and BDI confirmed its validity. Extraction method of the 12 items MSPSS using principle axis factoring with direct oblimin rotation converged into three factors of perceived social support (Family, Friends and Significant Others) with reliability coefficients of 0.88, 0.82 and 0.94, respectively. Conclusion: The Malay version of the MSPSS demonstrated good psychometric properties in measuring social support among a group of medical students from Faculty of Medicine, University Malaya and it could be used as a simple instrument on young educated Malaysian adolescents.